The Determinants of International Remittances in Developing Countries - Adams, Richard H., Jr. (2012)
What causes developing countries to receive different levels of international remittances? This paper addresses this question by using new data on such variables as the skill composition of migrants, poverty, and interest and exchange rates to examine the determinants of remittances. The paper finds that the skill composition of migrants does matter in remittance determination. Countries which export a larger share of high-skilled (educated) migrants receive less per capita remittances than countries which export a larger proportion of low-skilled migrants. It also finds that the level of poverty in a labor-sending country does not have a positive impact on the level of remittances received.